A study of cognition and behaviour in top management team interaction - Johnson, Phyllis (Cranfield University, 1998)
This thesis is concerned with strategy development processes in top management teams. It focuses on an explanation of consensuality in these teams; in particular, collectivc cognition and its relationship to convergent behaviour. Four different explanations of the nature of collective cognition and its rdationship to convergent behaviour were established in a review of the extant literature. These explanations were operationalised in the lorm of four propositions that wcre tested using a progressive case study design. In total three case studies were conducted. The first case, University Business School, was used as a pilot and helped to generate a more concrete operationalisation of three of the four. propositions. These were then examined and refined in a second case study; Colour Scheme. The third and final case, Construct Chemicals, was conducted longitudinally over time and tested these relined propositions. In all of the cases, data was collected in a similar way. That is, tcam members were intcrviewcd both belore and after importl1nt strategy development meetings. During these interviews, team members' views about their strategic issue were approximated using a cognitive mapping technique. Other additional data were also collectedl1t this time. The behaviour exhibited during team meetings was observed and discussions tape recorded. In the first two cases, only one meeting was attended, whereas in the tinal case four meetings were attended. These qualitative data were analysed to ascertain the presence and nature of collective cognition in the teams and to explore the extent to which this collective or indeed individual cognition was retlected in the behaviour observed in the team environment during periods of strategy development. It was established that in the organisations studied, collective cognition existed in various forms within dyads or subgroups within the top teams. However, several context dependent contingent variables were found to affect the development of collective cognition in the teams. Equally, a range or context specific contingencies mediated the relationshipbetween cognition and behaviour in the top team environment. All of these variables were built into a complete framework that represented the data collected.